2019
DOI: 10.1248/yakushi.19-00091
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research on the Effects of Differences in Properties of External Preparations for Skin on Application Amount: An Exploratory Investigation of the Relationship between the Base Usability and Application Amount by Questionnaire in Adult Subjects

Abstract: Compared to oral medication, the base plays a large role in the external preparation for skin, and dermatologists select the dosage form based on understanding of the eŠect of the base as well as according to skin symptoms and conditions, application site, age, season, etc. Further, in treatment with external preparations, it is important for patients to understand the application method and continue to apply an adequate amount to achieve the treatment goal. However, there is little evidence regarding the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The 1/3 FTU equivalent dose was selected as "a usual dose in clinical practice" because it was considered appropriate by patients who had not received any dosage instructions from their treating clinician. 10 The results after twice daily treatment with the moisturizer showed that the dry symptoms of the skin in the 20,21 In this study, however, the treatment effect of a 2 FTU equivalent dose was not considered as this is considered to be an excessive amount for application, and it will not remain on the skin because a portion of the coating drug attaches to clothes daily life.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The 1/3 FTU equivalent dose was selected as "a usual dose in clinical practice" because it was considered appropriate by patients who had not received any dosage instructions from their treating clinician. 10 The results after twice daily treatment with the moisturizer showed that the dry symptoms of the skin in the 20,21 In this study, however, the treatment effect of a 2 FTU equivalent dose was not considered as this is considered to be an excessive amount for application, and it will not remain on the skin because a portion of the coating drug attaches to clothes daily life.…”
Section: Discussionmentioning
confidence: 89%
“…The 1/3 FTU equivalent dose was selected as “a usual dose in clinical practice” because it was considered appropriate by patients who had not received any dosage instructions from their treating clinician. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lotion is especially convenient for use on the scalp (or other site with hair), or to cover large areas because it has low viscosity and is easy to spread. 1,2) The main component of lotion is water, and three types of lotion exist: solution, suspension, and emulsion. Drugs with low water solubility are hard to formulate in solution-type lotions without the use of solubilizing solvents/agents and procedures; therefore, emulsion-type lotion is especially attractive for oilsoluble drugs.…”
Section: Introductionmentioning
confidence: 99%